Baryon-photon interactions in resummed kinetic field theory - Kostyuk, Ivan; Lilow, Robert; Bartelmann, Matthias (Journal of cosmology and astroparticle physics, 2023)
We explore how interactions between baryons and photons can be incorporated into Kinetic Field Theory (KFT), a description of cosmic structure formation based on classical Hamiltonian particle dynamics. In KFT, baryons are described as effective mesoscopic particles which represent fluid elements governed by the hydrodynamic equations. In this paper, we modify the mesoscopic particle model to include pressure effects exerted on baryonic matter through interactions with photons. As a proof of concept, we use this extended mesoscopic model to describe the tightly coupled baryon-photon fluid between matter-radiation equality and recombination. We show that this model can qualitatively reproduce the formation of baryon-acoustic oscillations in the cosmological power spectrum.
Gesehen am 17.06.2024